Perception of employees on nepotism practices: a case study in management department of UiTM Kota Kinabalu / Nor Ezureen Jaludin and Sulaimie Hashim - Jaludin, Nor Ezureen; Hashim, Sulaimie (2016)
According to Hoctor (2012), nepotism in organizations means hiring individuals not on the basis of legal rules, but also based on relations. It comes from the Italian word for nephew. Nepotism is a kind of favoritism that affects the employee's performance. Due to nepotism, the employees leave the organization or are expelled from it. Many researchers have found that nepotism is a common phenomenon that occurs in small organizations in developing countries, (Arasli and Turner, 2000, cited in A.G. Rowshan, M. Ghasemnezhad, and Z. Hemmat, 2014). According to Harnandez and Page (2006), as cited in A.G. Rowshan, et al. (2014), nepotism is considered to be efficient when it is used appropriately. But when it causes conflicts of interest, homogeneity, inertia, and legal complications, it is treated as inefficient nepotism. Researchers had mentioned that nepotism in organization occurred due to several circumstances. One of circumstance is nepotism occurred in organization because of the experience and education background. Mulder (2008), as cited in A. Hoctor (2012), claims that people who are practicing nepotism are very often seen as unable and incompetent in doing their jobs. However, Bellow (2003), as cited in A. Hoctor (2012), argues that a Nepos would not take a position that he is highly unqualified for as this would only result in huge embarrassment if he failed.